Disseminated tuberculosis infection : a super 18F-FDG PET/CT appearance. - Nordin, Abdul Jalil; Rossetti, Claudio; Abdul Rahim, Noraini (Springer Verlag, 2009)
A 28-year-old immigrant presented with a 2-week history of throbbing headache. Contrast-enhanced computed tomography (CECT) examination showed multiple brain abscesses. He is a known defaulter from miliary tuberculosis treatment. 18F-FDG PET/CT demonstrated multiple visually high metabolic activity lesions disseminated in the brain, thorax, abdomen and pelvis [1]. The maximum standard uptake values (SUVmax) of these lesions were substantially > 3.0 and comparable to the uptake of FDG-avid malignant lesions. These findings demand careful image interpretation implicating false-positive results [2, 3]. Our case illustrates the usefulness of 18F-FDG PET/CT in mapping active tuberculous lesions which can be used for baseline study [4].